Expression of anaplastic lymphokinase and HER2/neu immunostaining in patients with breast carcinoma - Ali, Syed Naqeeb; Qureshi, Aneela; Fahim, Amin; Khoso, Muhammad Yousif (International Journal of Research in Medical Sciences, 2018)
Background: The diagnosis and prognosis of breast cancer is done with various immunomarkers including estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor-2 (HER2/neu), and Ki-67. The diagnostic utility of Anaplastic Lymphokinase (ALK) and HER2/neu should be explored for better management of breast carcinoma patients. So, the present study was designed to determine the expression of immunostaining with ALK and HER2/neu in patients with breast cancer and to compare the association of ALK expression and HER2/neu with clinicopathological parameters. Methods: This is a cross sectional multicenter study carried out from October 2016 to March 2017. A total of 140 subjects having breast carcinoma by using non-probability purposive sampling technique were selected. After taking informed consent, tissue samples were taken from received specimen of mastectomy for hematoxylin and eosin stain. The immunohistochemistry for ALK and HER2/neu were assessed on the paraffin blocks of the tumor. Results: Out of total 140 cases invasive ductal carcinoma (89%), invasive lobular carcinoma (8%), invasive medullary carcinoma (2.1%) and papillary carcinoma (0.7%) were seen. ALK expression was positive in 81 patients (58%) while HER2/neu expression was positive in 53 cases (38%). Significant association was observed between ALK expression with histological grade, lymph node involvement, skin involvement and necrosis. There was also a significant association was seen between HER2/neu expression with lymph node metastasis and necrosis. Conclusions: Present study shows higher expression of ALK when compared to HER2/neu expression in breast cancer patients.